IMPACT OF THE PUBLIC-PRIVATE PARTNERSHIP FOR PHOTOVOLTAIC SOLAR MINI-POWER PLANTS IN THE STATE OF PIAUÍ ON THE DEPARTMENT OF EDUCATION - Sousa, Daniel Leal; Lira, Marcos Antônio Tavares; de Moraes, Albemerc Moura (Seven Editora, 2025)
The growth in global energy demand, coupled with the environmental impacts caused by non-renewable sources, requires the adoption of public policies aimed at transitioning to renewable sources. In this context, photovoltaic solar energy has stood out as a strategic alternative, especially in regions with high solar incidence, such as the state of Piauí. This study aimed to quantify the economic impact of implementing mini photovoltaic solar power plants within the scope of public-private partnerships (PPPs) in the State of Piauí’s Department of Education (SEDUC). The results demonstrated savings in electricity costs (R 1,482,184.04 from March 2024 to February 2025). However, important challenges were identified: inadequate initial planning for the allocation of generation credits and delays in the project schedule. It is concluded that the adopted PPP model presents technical and economic viability, but needs adjustments to maximize its social and environmental impacts. DOI: https://doi.org/10.56238/sevened2025.036-142